Does road accessibility benefit rural poor? Evidence on the extent of household off-farm employment from 2004 to 2018. Issue 3 (9th March 2021) - Bai, Yunli; Zhou, Tianhao; Ma, Zhiyuan; Zhang, Linxiu
Abstract : Purpose: The purpose of this paper is to examine the role of infrastructure on the income growth and poverty reduction of rural household in China by estimating the impact of road accessibility on the extent of household off-farm employment and its heterogeneous effects among the groups with different income level and earning capacity. Design/methodology/approach: Using nationally representative panel data collected in 100 villages about 2000 households across five provinces in 2005, 2008, 2012, 2016 and 2019. This study adopts Tobit model with panel data, zero-inflated Poisson model and static nonbalanced panel model to yield consistent results. Findings: We find that road accessibility generally has no effect on the number of off-farm laborers and duration of off-farm employment. However, road accessibility is not beneficial for the households in the low-income villages or with low educational attainment, but it benefits the households in the high-income villages by promoting local off-farm employment or with high educational attainment by increasing the duration of migrant off-farm employment. Originality/value: This study identifies the heterogeneous effects of road accessibility on the extent of off-farm employment among rural households, which narrows the research gap and enriches the literature. The empirical findings imply that road accessibility widens the gap between rich and poor in off-farm employment, which is of great important to the alleviation of relative poverty after 2020 in China.